The Impact of the Menstrual Cycle on Athlete Self-Efficacy - Alya Daviyati; Tite Juliantine; Jajat Darajat Kusumah Negara; Sucipto (Universitas Negeri Semarang, 2026)
Menstrual cycle fluctuations shape the physiological and psychological landscape of female athletes, yet self-efficacy a central construct in sport psychology remains under-theorized at this intersection. Comprehensive synthesis integrating bibliometric trends with systematic evidence is absent. This study conducted a bibliometric-systematic literature review examining menstrual cycle effects on self-efficacy in female athletes from 2010 to April 2026. We analyzed 1,446 peer-reviewed articles from 809 Scopus-indexed journals using bibliometrix (R) version 4.1.4 and igraph. Quality assessment employed a hybrid instrument integrating CASP, Cochrane RoB 2.0, JBI, and a menstrual-cycle-specific criterion (κ=0.82). Six research questions addressed cycle-phase effects, measurement validity, sport-discipline variance, cultural moderators, age-level differences, and policy implications. Publication output grew exponentially from 35 articles in 2010 to 245 in 2025 (annual growth rate 5.22%), with 59.6% concentrated in 2021-2026. Logistic modeling projected peak productivity at 2026.4 (R²=0.660). Geographic concentration in North America and Europe reached 78.1%; Southeast Asia showed near-zero representation. Five thematic clusters emerged: Physiological-Hormonal, Applied Sports Activity, Psychosocial Factors, Reproductive Health, and Methodological. Of 1,446 articles, 167 (11.5%) satisfied all four core constructs (menstruation × athlete × female × self-efficacy). A central paradox emerged: 52.1% discussed self-efficacy or confidence, but only 4.7% used